2005
DOI: 10.1111/j.1600-051x.2005.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of periodontal pathogens in Brazilians with aggressive or chronic periodontitis

Abstract: These data support the hypothesis of differences between populations in the prevalence of periodontopathic bacteria and of greater attachment loss in sites infected with highly leucotoxic A. actinomycetemcomitans. Detection of highly leucotoxic A. actinomycetemcomitans in children and adolescents may be a useful marker for aggressive periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
140
4
20

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(186 citation statements)
references
References 36 publications
22
140
4
20
Order By: Relevance
“…Additionally, such variations in the global distribution of periodontopathic bacteria could be important in the epidemiology and the treatment of periodontal diseases. In view of the limited data available on the Brazilian distribution of A. actinomycetemcomitans in chronic periodontitis subjects 5,7,22,23 and as this bacterium was also considered a true pathogen, we examined the occurrence of A. actinomycetemcomitans in Brazilian subjects with mild, moderate and severe chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, such variations in the global distribution of periodontopathic bacteria could be important in the epidemiology and the treatment of periodontal diseases. In view of the limited data available on the Brazilian distribution of A. actinomycetemcomitans in chronic periodontitis subjects 5,7,22,23 and as this bacterium was also considered a true pathogen, we examined the occurrence of A. actinomycetemcomitans in Brazilian subjects with mild, moderate and severe chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Particularly, in the oral cavity A. actinomycetemcomitans has been strongly associated with aggressive periodontitis in several epidemiological studies, however, less investigated in chronic periodontitis patients. [3][4][5][6][7][8][9][10] This bacterium expresses several putative virulence factors which enable it to colonize the oral cavity, invade periodontal tissues and evade host defenses. 11 Additionally, different serotypes of A. actinomycetemcomitans have been shown to be associated with periodontal health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…Localized aggressive periodontitis is mainly associated with the bacteria Aggregatibacter actinomycetemcomitans (41,42) , while generalized aggressive periodontitis is strongly associated with specific bacteria such as Porphyromonas gingivalis, Tannerella forsythia (43,44) and Aggregatibacter actinomycetemcomitans, Gram-negative coccobacillus, capnophile, microaerophilic (45) . Microorganisms produce several virulence factors that could be involved in the destruction of periodontal tissues.…”
Section: Microbiologymentioning
confidence: 99%
“…The polymerase chain reaction (PCR) method has been applied as a technique for the detection of A. actinomycetemcomitans in subgingival biofilm samples and saliva (35,36,39). Several studies have shown that this methodology appears to have a great potential in the microbiological diagnoses of periodontal diseases and detection of periodontal pathogens directly in subgingival biofilm samples (6,7,14,33,38).…”
Section: Introductionmentioning
confidence: 99%